2010
DOI: 10.1093/toxsci/kfq023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term AZT Exposure Alters the Metabolic Capacity of Cultured Human Lymphoblastoid Cells

Abstract: The antiretroviral efficacy of 3′-azido-3′-deoxythymidine (AZT) is dependent upon intracellular mono-, di-, and triphosphorylation and incorporation into DNA in place of thymidine. Thymidine kinase 1 (TK-1) catalyzes the first step of this pathway. MOLT-3, human lymphoblastoid cells, were exposed to AZT continuously for 14 passages (P1–P14) and cultured for an additional 14 passages (P15–P28) without AZT. Progressive and irreversible depletion of the enzymatically active form of the TK-1 24-kDa monomer with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Cell cycle abnormalities induced by AZT have been previously observed in human HL60 (Roskrow & Wickramasinghe, 1990), Jurkat (Wu et al, 2004), Hela (Olivero et al, 2005) and lymphoblastoid cells (Olivero et al, 2010). Our results showed that the combination of AZT and emodin caused an accumulation of K562/ADM cells in S phase, which is consistent with Oliver's findings (Olivero et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cell cycle abnormalities induced by AZT have been previously observed in human HL60 (Roskrow & Wickramasinghe, 1990), Jurkat (Wu et al, 2004), Hela (Olivero et al, 2005) and lymphoblastoid cells (Olivero et al, 2010). Our results showed that the combination of AZT and emodin caused an accumulation of K562/ADM cells in S phase, which is consistent with Oliver's findings (Olivero et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the combination of AZT and emodin caused an accumulation of K562/ADM cells in S phase, which is consistent with Oliver's findings (Olivero et al, 2010). These results suggest that the regulation of cell cycle progression may be an important factor in the inhibition of cell growth in K562/ADM cells.…”
Section: Discussionsupporting
confidence: 92%
“…The inhibition of herbal components liquiritigenin and isoliquiritigenin towards the metabolism of hypnotic agent propofol limited the co-utilization of these two herbal components and propofol 13 . The dose beyond the efficient concentration of AZT can induce the genotoxicity and minimum cell death 14 . AZT has a narrow therapeutic index, and slight alteration of AZT concentration will exceed the minimal toxicity concentration of AZT.…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicate that the expression of TK1 gene and protein as well as its enzymatic activity is inhibited in THLE2 cells and elevated in HepG2 cells following AZT treatment. The suppression of TK1 results in a decreased activation of AZT, and consequently, decreased AZT incorporation into DNA (Fang and Beland 2009; Olivero et al 2010). Importantly, it remains to be established whether the observed induction of TK1 expression may lead to an increase in the intracellular concentration of AZT 5′-triphosphate.…”
Section: Discussionmentioning
confidence: 99%